The Effect of Fraud Triangle and Internal Control on Financial Statement Fraud with Intellectual Capital as A Moderating Variable - Nurul Rahmawati; Sri Yuli Ayu Putri (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Financial statement fraud in the banking sector poses a serious threat to national financial stability. This study aims to analyze the effect of the Fraud Triangle (pressure, opportunity, and rationalization) and internal control on financial statement fraud, and to examine the role of intellectual capital as a moderating variable. A quantitative approach was employed using secondary data from the financial statements of 14 banking companies listed on the Indonesia Stock Exchange (IDX) over the period 2020–2024 (65 observations), selected through purposive sampling. Financial statement fraud was measured using the F-Score model, while intellectual capital was assessed using the Value Added Intellectual Coefficient (VAIC) method. Data were analyzed Fthrough multiple linear regression and Moderated Regression Analysis (MRA) using SPSS 27. The results indicate that financial target and bonus mechanism have a positive and significant effect on financial statement fraud, whereas nature of industry and the proportion of independent commissioners show no significant effect. Simultaneously, all four variables jointly exert a significant effect, explaining 48.0% of the variance. Intellectual capital is proven to moderate the relationships between financial target, bonus mechanism, and the proportion of commissioners with financial statement fraud, but fails to moderate the relationship involving the nature of industry. These findings underscore that financial pressure and performance-based incentives are the primary fraud risk factors in banking, necessitating a balanced remuneration system and strengthened intellectual capital as key mitigation strategies.